Subcellular localization of neuronal nuclei (NeuN) antigen in size and calcitonin gene-related peptide (CGRP) populations of dorsal root ganglion (DRG) neurons during acute peripheral inflammation. (24th August 2021) - Anderson, Michael B.; Das, Subhas; Miller, Kenneth E.
Highlights: Neuronal Nuclei (NeuN) protein is expressed in the nucleus and cytoplasm of DRG neurons. Increased NeuN/FOX-3 expression indicates a robust DRG neuronal response at the peak swelling timepoint of CFA-induced acute inflammation. No morphologic signs of nuclear shrinking, chromatin condensation, or DNA fragmentation were observed in DRG neurons of any inflammatory group. These data suggest that there are no signs of DRG neuronal suffering or injury at the 48-h timepoint of the AIA model in the hind paw of the rat. Abstract: Pseudo-unipolar cell bodies of somatosensory primary neurons are located in the dorsal root ganglia (DRG). The somatic and peripheral domains of DRG neurons are often studied in sensory pain research to understand molecular mechanisms involved in the activation of pain and maintenance of inflammation. Adjuvant-induced arthritis (AIA) is an inflammatory model that elicits a robust and rapid onset immune response with a maximal swelling period of 24−48 h and persisting for several weeks. The AIA model in the hind paw of the rat elicits a potent inflammatory response of the dermis and epidermis, leading to protein expression changes for sensitization of many DRG neurons; however, it is unknown if the AIA model in the hind paw of the rat induces DRG neuronal injury, necrosis, or apoptosis at the somatic level. Neuronal nuclei (NeuN) antigen is a biomarker for post-mitotic neurons, neuronal identification, protein alterations, injury, and loss. Calcitonin gene-related peptide (CGRP) is expressed in C and Aδ DRG neurons, a subset of DRG neurons known to play a role in peripheral sensitization. The focus of this research was to evaluate the expression pattern of NeuN immunoreactivity, in size (soma) and CGRP subpopulations of DRG neurons in naïve and inflamed groups. Confirmed by both immunofluorescence and immunoprecipitation, DRG neuronal expression of NeuN was localized to nuclear and cytoplasmic subcellular compartments. NeuN increased within the nucleus of small CGRP positive DRG neurons during inflammation, indicating a potential role for NeuN in a subset of nociceptive neurons.